2021
DOI: 10.3390/su13158492
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Supply Chain Risk Management Approach for Lean Green Performance Based on AHP, RCA and TRIZ: A Case Study

Abstract: The purpose of this research work is to provide supply chain managers with a formal and generalizable approach that furnishes accurate guidelines to achieve a 2D performance integrating both Lean and Green. Despite the fact that several research works have been conducted in the framework of Lean and Green, at a conceptual level, the relationship between both paradigms is still ambiguous. Furthermore, the literature revealed a lack of relevant and generalizable approaches that explicitly demonstrate how to succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Unlike (Ruiz 2020;Ruiz and Stupariu 2021), it is demonstrated that the COVID-19 pandemic and crisis led to the reduction of green trade and green employment-as a result of the decrease in government financing. Unlike (Arcese et al 2020;Baggio and Valeri 2020;Elmo et al 2020;Essaber et al 2021;Mensi et al 2022;Valeri 2021), it is substantiated that financial risk management of the green economy (amid the pandemic and crisis) is allowed by green investments, the increase in which could ensure the increase in the global green economy's sustainability and the reduction of its disproportions among regions of the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike (Ruiz 2020;Ruiz and Stupariu 2021), it is demonstrated that the COVID-19 pandemic and crisis led to the reduction of green trade and green employment-as a result of the decrease in government financing. Unlike (Arcese et al 2020;Baggio and Valeri 2020;Elmo et al 2020;Essaber et al 2021;Mensi et al 2022;Valeri 2021), it is substantiated that financial risk management of the green economy (amid the pandemic and crisis) is allowed by green investments, the increase in which could ensure the increase in the global green economy's sustainability and the reduction of its disproportions among regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…The essence of financial risks consist of the reduction in financing of the green economy (Chiang 2021;Hagspiel et al 2021;Mezghani et al 2021;Nagy et al 2021;Yang et al 2021;Zhao et al 2021). Accordingly, the approach to financial risk management implies an increase in green economy financing (Arcese et al 2020;Baggio and Valeri 2020;Elmo et al 2020;Essaber et al 2021;Mensi et al 2022;Valeri 2021).…”
Section: Theorymentioning
confidence: 99%
“…Various creative steps are extended through innovative solutions to produce more competitive UAV designs. AHP was proposed by Thomas, L. Saaty, a professor at the University of Pittsburgh in the United States in 1971, when he was engaged in research on contingency planning for the US Department of Defense [4] It mainly assists decision-making through multiple evaluation criteria in the face of various uncertain results. This study found that although ARIZ has high innovative breakthrough thinking assistance, it is prone to produce too many solutions, and AHP can help this system to approach perfect solutions, ARIZ will produce countless inventive solutions by comparing the fundamental contradiction of the problem and the technical contradiction.…”
Section: Icpmmt-2023mentioning
confidence: 99%
“…Preventive measures to manage risks are a form of insurance applied to assumed but unspecified events for which the probabilities and financial consequences are unknown. Various authors have studied the classification of the causes of supply chain risks in particular logistics, such as Essaber and Fuchs, whose work is one of the most generalized [149, 153,154]. Based on these studies, four main causes of risk in logistics are outlined as shown in Figure 7.…”
Section: Risk Management In Logisticsmentioning
confidence: 99%